SANISAND-F: Sand constitutive model with evolving fabric anisotropy - Petalas, Alexandros L.; Dafalias, Yannis F.; Papadimitriou, Achilleas G. (International journal of solids and structures, 2020)
In order to incorporate the very important role of evolving fabric anisotropy on the mechanical response of sand, a constitutive model is developed within the frameworks of Bounding Surface plasticity and Anisotropic Critical State Theory in multiaxial stress space. The main new constitutive ingredient is a fabric anisotropy variable A, a scalar measure of the relative orientation between an evolving fabric tensor F and the deviatoric plastic strain rate direction. The variable A affects scalar ingredients of the model quantifying the plastic strain rate, i.e. the plastic modulus and the dilatancy. A comprehensive calibration procedure is fully described and an extensive validation is performed against a very large dataset from 55 monotonic element tests on Toyoura sand provided by various laboratories, loaded under drained and undrained conditions. The introduction of A into the model is the main reason why successful simulation of data is achieved for loading at various orientations of the stress tensor under otherwise same initial conditions of void ratio and confining pressure, and this even if the data often exhibit huge difference of response because of the difference in loading orientation.